Весьегонская волчица: [Сборник] / Б. Т. Воробьев - Воробьев Борис Тимофеевич (Библ. сер., 1989)
Экземпляры: ф.10 (20200311) / Инвентарный номер: 20283 / Цена: 3.00 / Сис.шифр: 28.68 / Авт.знак: В75 / ББК: 28.68